Influence of different mating ratio on the fertility and hatchability of “TANUVAS Namakkal Quail-1 breeders” - Bharat, Khandare Tejashwini; Moorthy, M; Rajendran, K; Sivakumar, K (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological experiment was conducted to study the effect of different mating ratio on fertility and hatchability of TANUVAS Namakkal quail-1 breeders. The experiment was conducted by using two hundred and fifty adult birds of the age 15-25 weeks (males:25 and females:125) and 35-45 weeks (males:25 and females:125) TANUVAS Namakkal quail-1 breeders. The different male: female ratios viz. T1 (1:2), T2 (1:3), T3 (1:4), T4 (1:5) and T5 (1:6) were maintained in cages separately. All the birds were reared as per the standard management procedure and fed with Japanese quail breeder diet. The fertile eggs were collected from each male: female ratio separately for 28 days period. Eggs were set in the incubator and per cent hatchability, infertile, embryonic mortality and dead-in-shell were studied. The results of the experiment revealed that the hatchability was highly significant (P<0.01) in T3 group (77.62%) with a mating ratio of 1:4 in 15 to 25 weeks age group and in T2 group (72.83%) with a mating ratio of 1:3 in 35 to 45 weeks age group. From this study it could be concluded that the optimum mating ratio for “TANUVAS NAMAKKAL Quail-1” breeder for younger age group is 1:4 and for older age group is 1:3.